A real-time ratiometric fluorescent probe for imaging of SO2 derivatives in mitochondria of living cells. Issue 39 (18th July 2019) - Shi, Junwei; Shu, Wei; Tian, Yong; Wu, Yulong; Jing, Jing; Zhang, Rubo; Zhang, Xiaoling
Abstract : A real-time ratiometric fluorescent probe (IN-CZ ) for highly selective detection of sulfite was designed and synthesized, which is based on modulating the intramolecular charge transfer of the hemicyanine dye platform. Abstract : A real-time ratiometric fluorescent probe (IN-CZ ) for highly selective detection of sulfite was designed and synthesized, which is based on modulating the intramolecular charge transfer (ICT) of the hemicyanine dye platform. The mechanism of using the probe is mainly through the Michael addition that occurs betweenIN-CZ and sulfite with a detection limit of 2.99 × 10 −5 M.IN-CZ displays a fast response (within 1 minute) and is highly selective for SO3 2− /HSO3 − over ROS, biologically relevant ions, biological mercaptans and other reactive species. More importantly, IN-CZ was suitable for ratiometric fluorescence imaging in living cells, by real-time monitoring of SO3 2− /HSO3 − changes in mitochondria targeted in living cells.